PGE2 Supplementation of Oocyte Culture Media Improves the Developmental and Cryotolerance Performance of Bovine Blastocysts Derived From a Serum-Free in vitro Production System, Mirroring the Inner Cell Mass Transcriptome - Charpigny, Gilles; Marquant-Le Guienne, Brigitte; Richard, Christophe; Adenot, Pierre; Dubois, Olivier; Gélin, Valérie; Peynot, Nathalie; Daniel, Nathalie; Brochard, Vincent; Nuttinck, Fabienne (Frontiers in Cell and Developmental Biology, 2021)
The culture media used throughout the in vitro production (IVP) of bovine embryos remain complex. The serum added to culture media in order to improve embryo development negatively impacts the cryotolerance of blastocysts. Periconceptional prostaglandin E2 (PGE2) signaling is known to exert prosurvival effects on in vitro-generated blastocysts. The purpose of the present study was to evaluate the effects on developmental and cryotolerance performance of a serum-free (SF) IVP system that included defined oocyte culture media supplemented or not with PGE2, versus serum-containing (SC) IVP. RNA-sequencing analysis was used to examine the gene expression of ICM derived under the different IVP conditions. We assessed the degree of cryotolerance of grade-I blastocysts during a three-day post-thaw culture by measuring survival and hatching rates, counting trophectoderm and inner cell mass (ICM) blastomere numbers . We also determined the proportion of ICM cells expressing octamer-binding transcription factor 4 protein (OCT4/POU5F1). We showed that grade-I blastocyst development rates under SF+PGE2 conditions were similar to those obtained under SC conditions, although the cleavage rate remained significantly lower. SC IVP conditions induced changes to ICM gene expression relative to several metabolic processes, catabolic activities, cell death and apoptosis. These alterations were associated with significantly higher levels of ICM cell death at day 7 post-fertilization, and lower survival and hatching rates after thawing. SF IVP conditions supplemented or not with PGE2 induced changes to ICM gene expression related to DNA replication, metabolism and double-strand break repair processes, and were associated with significantly larger ICM cell populations after thawing. SF+PGE2 IVP induced changes to ICM gene expression related to epigenetic regulation and were associated with a significantly higher proportion of ICM cells expressing OCT4. For the first time, our study thus offers a comprehensive analysis of the ICM transcriptome regulated by IVP culture conditions in terms of the cellular changes revealed during culture for three days after thawing.